VanZ Reduces the Binding of Lipoglycopeptide Antibiotics to Staphylococcus aureus and Streptococcus pneumoniae Cells - Vimberg, Vladimir; Zieglerová, Leona; Buriánková, Karolína; Branny, Pavel; Balíková Novotná, Gabriela (Frontiers in microbiology, 2020)
vanZ, a member of the VanA glycopeptide resistance gene cluster, confers resistance to lipoglycopeptide antibiotics independent of cell wall precursor modification by the vanHAX genes. Orthologs of vanZ are present in the genomes of many clinically relevant bacteria, including Enterococcus faecium and Streptococcus pneumoniae; however, vanZ genes are absent in Staphylococcus aureus. Here, we show that the expression of enterococcal vanZ paralogs in S. aureus increases the minimal inhibitory concentrations of lipoglycopeptide antibiotics teicoplanin, dalbavancin, oritavancin and new teicoplanin pseudoaglycone derivatives. The reduction in the binding of fluorescently labeled teicoplanin to the cells suggests the mechanism of VanZ-mediated resistance. In addition, using a genomic vanZ gene knockout mutant of S. pneumoniae, we have shown that the ability of VanZ proteins to compromise the activity of lipoglycopeptide antibiotics by reducing their binding is a more general feature of VanZ-superfamily proteins.
Keywords: Staphylococcus aureus; VanZ; antibiotic resistance; Streptococcus pneumoniae; lipoglycopeptide antibiotics